Analisis Spasial Proyeksi Populasi di Kabupaten Bombana hingga Tahun 2045 Menggunakan Model Pertumbuhan Aritmatika dan Eksponensial - Huda, Muhammad Nurul; Anwar, Nur Kahfi Mukhlisin; Rizqullah, Rafi Sulthan; Putri, Shalsabilla Aulia; Rahma, Nisrina Gina (Journal of Geographical Sciences and Education, 2026)
Population growth projection in Bombana Regency up to 2045 is important because population increase is not accompanied by an even spatial distribution across sub-districts, which may lead to different levels of regional pressure in the long term. Population projection based on arithmetic and exponential growth models integrated with Geographic Information Systems (GIS) is applied to describe variations in the spatial patterns of population growth at the sub-district level and to identify differences in projection results under different growth assumptions. Knowledge of population growth trends and spatial distribution is required to assess the direction of population development in the central to western parts of Bombana Regency, which grow faster than coastal and island areas, as a basis for long-term regional and spatial planning.